PENERAPAN PEMBELAJARAN KOOPERATIF TIPE SNOWBALLTHROWINGUNTUK MENGURANGI KESALAHAN MENYELESAIKAN SOAL PERSAMAAN KUADRAT SISWA KELAS XSMK NEGERI 1 JEMBER TAHUN AJARAN2012/2013 - Isnaini, Deasty Sujius; Sugiarti, Titik; Kristiani, Arika Indah (Department of Mathematics Education , University of Jember, 2013)
Abstract.Snowball throwing is one of the cooperative learning methods. Snowball throwing is packed in the game with simple rules that are easy to apply in learning mathematics.This research is a classroom action research which is purposed to reduce errors in solving quadratic equations with cooperative learning type snowball throwing. The subject of the research is the students of X AP 3 grade SMK Negeri 1 Jember in the academic year 2012/2013. The data which is collected by using observation, interview, and test method. The results of the research showed an increasing in student activity, namely 74.67% in the first cycle and 80.63% in the second cycle. The total percentage of errors decreased, namely 70.18% in the preliminary test, 45.28% in the first cycle test, and 11.83% in second cycle test. Based on the result of the research, it can be concluded that cooperative learning type snowball throwing can increase the learning activity, reduce errors in solving quadratic equations, and decrease percentage of errors. Key Words:snowball throwing, cooperative learning,reduce errors in solving, quadratic equations